Economic Uncertainty and Monetary Policy Effectiveness: A Comparative Study between High and Low Uncertainty Countries - Bogari, Adel (Journal of Ecohumanism, 2024)
This study examines the impact of economic uncertainty on monetary policy effectiveness, as measured by inflation, in 21 countries observed during the period stretching from 1997 to 2022. The study uses a Generalized Method of Moments (GMM) model on full, high and low uncertainty countries. Our results indicate that uncertainty has a significant positive impact on inflation. The results also show that central banks have adopted a cautious approach in response to these shocks, and that monetary policy moderates the negative effects of economic uncertainty. Finally, we found similar results for countries with low vs. high economic uncertainty levels. The findings can be worthwhile to sketch proper monetary policy under uncertainty to lessen monetary policy effectiveness. This study suggests that it is important to note that, in times of high economic uncertainty, monetary policy can be effective when a reactive monetary policy acts as an economic stabilizer and inflation controller. Contribution/ Originality: This study is one of the very few studies investigating the relationship between economic uncertainty and monetary policy effectiveness. It does so using the Generalized Method of Moments (GMM) model in high uncertainty versus low uncertainty countries, thus contributing to our understanding of monetary policy effectiveness under uncertainty.Economic uncertainty